The Morphotectonic units of Ikaria island – Contribution in the natural hazards research - Efraimiadou, H.; Lozios, St.; Evelpidou, N. (Bulletin of the Geological Society of Greece, 2011)
Present morphological and tectonic image of Ikaria island is the complex result of both the tem-poral evolution of the island, as part of the geodynamical evolution of the Hellenic Arc, especially that of the last stages (from the upper Miocene and after), and the exogenous factors. Also human impact functions as an additional parameter for the formation of Ikaria geoenvironment. According to field data and their analysis, computing and estimation which took part with the use of modern technologies (use of GIS, analysis of geographical and descriptive databases) the mor-photectonic units of Ikaria Island were defined. The definition of the morphotectonic units was based on their special features and more precisely on the lithological differentiation (granite, metamorphic rocks and post alpine formations) as well as the complex ductile and brittle structures (large scale ductile shear-zones and brittle detachment faults, normal faults, strike-slip transfer faults and join sets) and the morphological features (slope distribution, asymmetry of the drainage system, planation surfaces, morphological discontinuities etc). The synthesis of the special features of each morphotectonic unit in combination with the human impact (fires, overgrazing etc), defines the kind, the intensity and the geographical localization of the natural hazards which occur in various sites of the island, such as landslides, erosion, floods, seismic activity, relief changes, coastline changes etc.